Ultrasound predictors of difficult airways - E. G. Usikyan; A. Yu. Zaytsev; K. V. Dubrovin; V. A. Svetlov; D. R. Sheptalina (Вестник анестезиологии и реаниматологии, 2023)
The objectives was to evaluate the effectiveness of diagnosing predictors of difficult airways with ultrasound.Materials and methods. 70 patients were examined. Before the surgery, we assessed the risk of difficult intubation by the LEMON scale and ultrasound methods using the following criteria: tongue thickness, vertical distance from the highest point of the hyoid bone to the mandible, neck  soft tissue thickness, and epiglottis thickness. The diagnostic ability of the LEMON scale and ultrasound diagnosis of difficult laryngoscopy was  assessed by determining the sensitivity, specificity and cut-off point using the ROC-AUC analysis. Results. The analysis of the obtained data showed a higher sensitivity of ultrasound criteria for difficult airways compared with the LEMON scale.  Conclusion. Ultrasound diagnostic methods are effective for assessing difficult laryngoscopy. Ultrasound diagnostic criteria for difficult laryngoscopy  are more sensitive compared to the LEMON scale. Diagnostic criteria for difficult laryngoscopy are: tongue thickness > 61 mm, vertical distance  from the highest point of the hyoid bone to the mandible > 12.85 mm, neck soft tissue thickness > 5.15 mm, and epiglottis thickness > 2.85 mm.